Reflection seismic imaging of the upper crust in the Kristineberg mining area, northern Sweden - Dehghannejad, M.; Juhlin, Christopher; Malehmir, A.; Skyttä, P.; Weihed, P. (Elsevier, 2010)
The Kristineberg mining area is located in the western part of the Palaeoproterozoic Skellefte Ore District, one of the most important mining districts in Europe. As a part of a 3D geologic modeling project, two new reflection seismic profiles were acquired with a total length of about 20. km. One profile (HR), parallel to previous seismic profiles, was acquired using a 10. m receiver and source interval and crosses the steeply dipping structures of the Kristineberg mine. The other profile (Profile 2) runs perpendicular to all existing profiles in the area. Although the structural geology is complex, the processed seismic data reveal a series of steeply dipping to sub-horizontal reflections, some of which reach the surface and allow correlation with surface geology. Our general interpretation of the seismic images is that the Kristineberg mine and associated mineral horizon are located in the northern part of a series of steeply south dipping structures. Overall, main structures plunge to the west at about 30°-40°. Cross-dip analysis and reflection modeling were carried out to obtain the 3D orientation of the main reflections and to provide insight into the possible contribution of out-of-the-plane reflections. This helped, for example, to obtain the 3D geometry of a deep reflection that was previously interpreted as structural basement to volcanic rocks. The new reflection seismic profiles have improved our understanding of shallow geological structures in the area and in conjunction with recently acquired potential field data, magnetotelluric data and geological observations will help to refine previous 3D geologic modeling interpretations that were aimed at larger scale structures. © 2010 Elsevier B.V.